Dominance of human Influenza H1N1pdm09 in flu like patients during early two months of 2020 (Pulse, 2023)
Introduction:Influenza is a worldwide respiratory infectious disease which affect all age groups and associated with significant number of morbidity and mortality each year. The circulating subtypes varies countrywide yearly, and it helps policy maker to get preparedness for early effective management of influenza epidemics.Materials and methods Nasal swabs were collected from 463 patients in January and February 2020 presenting flu-like symptoms and Rapid Influenza Diagnostics Tests (RIDTs) were performed for influenza A & B screening as a routine test. Then influenza A subtyping was done by RT-PCR followed by gel electrophoresis of 27 influenza positive samples.Result Among 463 cases, 106 (22.9%) were Influenza positive with huge (99.06%) dominance of Influenza A. Subtyping of randomly selected outpatient derived 27 Influenza A positive cases showed flourishing presence of seasonal Influenza A/H1N1pdm09 (21; 77.8%).Conclusion This small study warrants further elaborate investigation to know circulating influenza A subtyping in the country which may assist health care providers in making treatment decisions and hence, appropriate patient management.Pulse Volume 12-14 2020-2022 p.4-9